2015
DOI: 10.1371/journal.pone.0133034
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Craving Related Brain Responses Using Real-Time fMRI in Patients with Alcohol Use Disorder

Abstract: LiteratureOne prominent symptom in addiction disorders is the strong desire to consume a particular substance or to display a certain behaviour (craving). Especially the strong association between craving and the probability of relapse emphasises the importance of craving in the therapeutic process. Neuroimaging studies have shown that craving is associated with increased responses, predominantly in fronto-striatal areas.Aim and MethodsThe aim of the present study is the modification of craving-related neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 50 publications
4
72
0
3
Order By: Relevance
“…Compared to both no feedback and sham feedback control groups, the real feedback group had reduced activation of VS after treatment. These results were similar to those reported by Karch et al (2015), who utilized two different control groups, one with false feedback and another with no feedback. The real feedback group exhibited lower activation in ACC, dlPFC, inferior temporal gyrus, MFG, and insula.…”
Section: Neuromodulatory Techniques For Treatmentsupporting
confidence: 89%
“…Compared to both no feedback and sham feedback control groups, the real feedback group had reduced activation of VS after treatment. These results were similar to those reported by Karch et al (2015), who utilized two different control groups, one with false feedback and another with no feedback. The real feedback group exhibited lower activation in ACC, dlPFC, inferior temporal gyrus, MFG, and insula.…”
Section: Neuromodulatory Techniques For Treatmentsupporting
confidence: 89%
“…with alcohol use disorder, enhanced prefrontal activation after neuro-feedback-training was associated with reduced craving [Karch et al, 2015]. Interestingly, excitatory stimulation of the PFC with transcranial direct current stimulation [Kekic et al, 2014] and transcranial magnetic stimulation [Uher et al, 2005] also reduced food craving and improved the self-reported ability to resist food in healthy women.…”
Section: Discussionmentioning
confidence: 98%
“…To date, several studies show that neurofeedback training causes behavioral effects that are specific to the functional role of the targeted cortical area (Weiskopf et al, 2004; Bray et al, 2007; Caria et al, 2007; Rota et al, 2009; Shibata et al, 2011; Scharnowski et al, 2012, 2015; Robineau et al, 2014; Koush et al, 2015; Scharnowski and Weiskopf, 2015). Even more importantly, real-time fMRI neurofeedback training has also been shown to have therapeutic effects in chronic pain patients (deCharms et al, 2005; Guan et al, 2015), Parkinson’s disease (Subramanian et al, 2011), tinnitus (Haller et al, 2010), depression (Linden et al, 2012; Young et al, 2014), obsessive-compulsive disorder (Scheinost et al, 2013, 2014), spider phobia (Zilverstand et al, 2015), and addiction (Li et al, 2013; Karch et al, 2015; Kirsch et al, 2015; Hartwell et al, 2016). Especially for clinical applications of neurofeedback it is crucial that the learning effects persist beyond the initial training period and that voluntary control transfers to situations without neurofeedback information.…”
Section: Discussionmentioning
confidence: 99%